On the Difficulty of Defining “Difficult” in Second-Language Vowel Acquisition - Munro, Murray J. (Frontiers in Communication, 2021)
Hierarchies of difficulty in second-language (L2) phonology have long played a role in the postulation and evaluation of learning models. In L2 pronunciation teaching, hierarchies are assumed to be helpful in the development of instructional strategies based on anticipated areas of difficulty. This investigation addressed the practicality of defining a pedagogically useful hierarchy of difficulty for English tense and lax high vowels (/i ɪ u ʊ/) by Cantonese speakers. Unlike their English counterparts, Cantonese high tense-lax pairs are allophonic variants with [ i u ] occurring before alveolars and [ ɪ ʊ ] before velars. Each tense-lax pair represents a “phonemic split” in which members of a single L1 category are realized contrastively in L2. Despite evidence that English tense-lax distinctions are challenging for Cantonese speakers, no previous empirical work has closely considered the problem from the standpoint of vowel intelligibility across multiple phonetic contexts and lexical items. In a picture-based word-elicitation task, 18 Cantonese-speaking participants produced 31 high-frequency CV and CVC words. Vowels were evaluated for intelligibility by phonetically-trained judges. A series of mixed-effects binary logistic models were fitted to the scores, with vowel quality, phonetic context (rhyme) and word as factors, and length of Canadian residence and daily use of English as co-variates. As expected, the general hierarchy of difficulty for vowels that emerged (/i/ > /u/ > /ʊ/ > /ɪ/) was complicated by large differences across phonetic contexts. Results were not readily explicable in terms of transfer; moreover, a clear lexical effect was observed, in that different words with the same rhyme were not produced with equal intelligibility. The most serious modelling complication was the sizeable inter-speaker variability in difficulties, which could not be accounted for by model co-variates. Although some difficulties were roughly systematic at the group level, it is argued that establishing a pedagogically useful hierarchy on such data would prove intractable. Rather, L2 learners might be better served by assessment and instructional targeting of their individual problem areas than by a focus on errors predicted from hierarchies of difficulty.